PERAN IBU DALAM PENERAPAN PENDIDIKAN SEKSUALITAS PADA ANAK USIA PRA SEKOLAH (Di TK SBI Kroyo ,Karangmalang, Sragen) - Retno Ambarwati (Universitas Muhammadiyah Semarang, 2013)
Background: Sexuality is a totality of expression of the individual as male or female, what is believed, thinking and feeling about him/herself, how to react to the environment, how to present yourself, how cultured and bersosial, social ethics, which characterize individual identity. Parents are very involved in providing information, referrals, and understanding of sexuality in child care. The problem, parents in this case the mother is still uncomfortable talking about matters related to sexuality to their children, because they think it's taboo,and yet needs to be given to children early on. Objective: To determine whether there is a significant positive relationship between level of education, knowledge and attitude of mothers about sexuality education with the application of sexuality education in pre-school age children. Methods: A cross sectional study design, the researchers used a technique of sampling Probability sampling with cluster sampling method. sample size of 60 persons mother graders K1 A, K1 B, and K2 A. As for the testing instrument of 20 respondents from K2 B class.The Result: there is a significant positive relationship between level of education with the implementation of Education sexuality (p = 0.010, α <0.05), level of knowledge of mothers with the application of sexuality education (p = 0.002, α <0.05), mother's attitude to the implementation Education sexuality (p = 0.002, α <0.05) F test analysis results count (p = 0.000, α <0.05) so that it can be concluded simultaneously independent variables significantly influence the dependent variable. Conclusion: The significant correlation between level of education, knowledge and attitude of mothers about sexual education with the application of sexuality education in pre-school age children in kindergarten Kroyo SBI, District Karangmalang, Sragen Regency. Keywords: Level of education, Knowledge, Attitudes, The application of preschool sexuality education